Analysis Of Factors That Drive Purchase Intention On The Local Brand Careso - Winarsih Winarsih; Fariha Azzahra; Dasa Amelia (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2025)
The positive growth of the local perfume industry is driven by increasing public interest in unique, high-quality, affordable fragrances that reflect local wisdom. Statista Market Insights projects that Indonesia's perfume market revenue will reach US440.9 million, or approximately Rp 6.9 trillion, by 2024, with 70% contribution from non-luxury perfumes. The current investigation is conducted to investigate the effect of Social media advertising, personal branding owner and influencer collaboration marketing on purchase intention of local brand Careso. A quantitative method framework was applied in this study. The sampling method implemented was purposive sampling, involving 96 respondents who actively accessed social media, particularly TikTok and Instagram. The data collection process was carried out through a structured questionnaire and subsequently analyzed with SPSS software, utilizing multiple linear regression analysis, t-test procedures and coefficient determination analysis. The findings indicated Social media advertising, personal branding owner and influencer collaboration marketing had a significant influence on purchase intention. But the coefficient of determination analysis shows the result r-square value of 0.238 its means that all independent variable has an influence on puchase intention anly 23,8% while the remaining 76,2% is influenced by other factors not observed in this research.